Effects of brief mindfulness intervention on mental fatigue and recovery in basketball tactical performance. - Shudian Cao; Jia Liu; Soh Kim Geok; He Sun; Xiaopeng Wang (PLoS ONE)
Objective The detrimental effects of mental fatigue (MF) have been established in sports, such as soccer, volleyball, and basketball. Mindfulness interventions are considered a promising method to help players counteract MF, but whether it could improve basketball tactical performance after MF in competition is not clear. This study aims to investigate the effect of brief mindfulness intervention on basketball tactical performance under MF. Method This study employed a cluster randomized controlled trial (cRCT) design. It involved 54 male basketball players aged 18 to 24 from three universities. The participants were randomly assigned to one of three groups: control group (CG), mental fatigue group (MFG), and mental fatigue-mindfulness group (MF-MG). Players in the MFG and MF-MG underwent a 30-minute Stroop task to induce MF. Subsequently, players in the MF-MG engaged in a 30-minute audio mindfulness intervention. Basketball tactical performance was assessed in the small side games (SSG). Results There were no significant differences in total tactics observed across groups and over time. However, when examining specific tactical sub-variables, significant differences were found in ball reversal, dribble penetration into the key area, and off-ball screen between the CG and MFG in the post-test. Furthermore, significant differences were noted in ball reversal, dribble penetration into the key area, on-ball screen, and off-ball screen between the MFG and MF-MG in the post-test. Conclusion The basketball tactical performances, particularly in areas such as ball reversal, dribble penetration into the key area, on-ball screen, and off-ball screen, were negatively impacted by MF. Notably, the brief mindfulness intervention effectively restored these performance aspects. This suggests that coaches and trainers should place increased emphasis on players' mental well-being and consider incorporating brief mindfulness interventions into their training programs. More studies that investigate mindfulness intervention on the comprehensive aspects of basketball performance should be focused on in the future.